Qualidade do sono materno não compromete o desenvolvimento neuropsicomotor infantil - SANTOS, Fabrícia Silvana Sarmento dos (2021)
Sleep is a complex biological process that is fundamental for organic balance and its restriction intervenes in people's physical and mental well-being, causing serious functional impairment. The quality of sleep, especially for mothers, directly affects the health status and quality of life of everyone around them. Damages in the mother-child relationship can trigger changes with negative repercussions on child development. Thus, this research aimed to investigate the relationship between maternal sleep quality and child neuropsychomotor development. This is a cross-sectional, descriptive-analytical and quantitative study, carried out with 121 mothers and 121 children, from August 2020 to January 2021, in a private pediatric institution in the city of Imperatriz, Maranhão. Data collection involved two steps: survey of sociodemographic, economic and perinatal data, and assessments of the quality of maternal sleep using the Pittsburgh Sleep Quality Index (PSQI) instrument, and that of the child through the Denver developmental screening test - Denver II. Mothers who obtained scores above five points were considered to have poor sleep quality and children had neuropsychomotor development classified as normal and non-normal. Descriptive analysis was performed using absolute and relative frequencies for all sociodemographic, perinatal, maternal sleep quality and DNPM variables. To assess possible associations between DNPM components (personal-social, fine-adaptive motor, language and gross motor), sociodemographic and perinatal variables in relation to maternal sleep quality, crude and adjusted binary logistic regression models were used. Variables that presented p-value ≤ 0.20 were included in the adjusted model. Odds ratios (OR) with 95% confidence intervals were also estimated. The project was approved by the Research Ethics Committee of the Federal University of Maranhão, under opinion no 3.820.879. The results showed that the mean maternal age was 29.2 years, most of which (91.7%) were in a stable relationship, 66.1% had higher education, 99.2% had regular prenatal care and 26.4% had risk in pregnancy. In terms of monthly family income, 44.6% received between one and five minimum wages. The analysis of sleep quality components in the last month showed that 71.1% of the mothers surveyed had poor sleep quality (PSQI >5). The analysis of neuropsychomotor development using the Denver II test evidenced the occurrence of delays in the language and gross motor components, in a reduced portion of 1.7% of the sample. Although these developmental delays have occurred in some children, there was no statistical significance for this association with the quality of maternal sleep. Associations between the PSQI indicator and sociodemographic/perinatal characteristics were also not identified. It is concluded, in this investigation, that there was no relationship between maternal sleep quality and child neuropsychomotor development.